Intravascular leukocyte migration through platelet thrombi: directing leukocytes to sites of vascular injury - Ghasemzadeh, Mehran; Hosseini, Ehteramolsadat (Thrombosis and Haemostasis, 2015)
Leukocytes recruitment to thrombi supports an intimate cellular interaction leading to the enhancement of pro-coagulant functions and pro-inflammatory responses at site of vascular injury. Recent observations of neutrophil extracellular traps (NETs) formation and its mutual reactions with platelet thrombi adds more clinical interest to the growing body of knowledge in the field of platelet-leukocyte crosstalk. However, having considered thrombus as a barrier between leukocytes and injured endothelium, the full inflammatory roles of these cells during thrombosis is still ill defined. The most recent observation of neutrophils migration into the thrombi is a phenomenon that highlights the inflammatory functions of leukocytes at the site of injury. It has been hypothesised that leukocytes migration might be associated with the conveyance of highly reactive pro-inflammatory and/or procoagulant mediators to sites of vascular injury. In addition, the evidence of neutrophils migration into arterial thrombi following traumatic and ischaemia-reperfusion injury highlights the already described role of these cells in atherosclerosis. Regardless of the mechanisms behind leukocyte migration, whether these migrated cells benefit normal homeostasis by their involvement in wound healing and vascular rebuilding or they increase unwilling inflammatory responses, could be of interest for future researches that provide new insight into biological importance of leukocyte recruitment to thrombi.
Keywords: Platelet-leukocyte crosstalk; NETs formation; intravascular leukocyte migration; neutrophil induced atherosclerosis